As temáticas água e crise hídrica no sistema estruturado de ensino em geografia no estado de Mato Grosso - Silva, Alexsandra Gomes Aquino da (2024)
In the teaching of Geography, water and water crisis are important and fundamental themes that need to be studied in all physical, chemical, socio-environmental, political and cultural aspects. Water is indispensable for the survival of life on Earth, its use and availability has caused tensions and concerns around the world. These themes are essential in pedagogical knowledge to develop a critical social posture of the main agents of learning, teachers and students, with participatory attitudes in the field of construction and perceiving the real problems of water supply. The research was built through a bibliographic analysis, with foundation and theoretical basis in the pedagogical proposal of the notebooks of the Structured System of Teaching Geography of the 1st, 2nd and 3rd grades of high school element. The themes were analyzed broadly in the notebooks, having essential functions in the debates related to water and water crisis to be observed, directed to students with mastery and conceptions capable of having repercussions on social critical reflections, contributing to the student being a competent citizen and capable of solving daily problems, considering the scope of the contents in the classroom. The work initially took place in a qualitative way, after an in-depth reading of the didactic notebooks, identifying the approach to the contents of water and water crisis, with the main study tool being the pedagogical teaching material applied in the school. The aim of the research is to analyze the contents, activities, images, subjects, discussions and conceptualizations of Geography made available by the Mato Grosso State Department of Education, addressed in the Structured Teaching System element. The results of the study indicate that the themes "water and water crisis" are treated with little relevance and in a superficial way, separating the contents established in the notebooks from the school practices of students and teachers. The specific concentration of meaningless content in high school interferes with the process of teaching and learning in school. An in-depth study of the contents when it comes to water and water crisis, problems caused by lack of water supply, which are experienced daily by local school communities, is essential.